(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
Nutrient deficiency is one of among major problems constraining the development of economically successful agriculture. Specifically, this resulted from lower crop performance. To enhance crop performance, the application of the newly recommended fertilizer rate is among the necessary measures. Hence, this pre-extension demonstration of the newly recommended fertilizer rate on maize and evaluated the change in its profitability. The demonstration was conducted at two farmers’ training centers and ten beneficiary farmers’ fields. Partial budget analysis was employed to evaluate the change in profitability from the new recommended rate. Based on the result, the average yield performances that were obtained from farmer’s fields were 40.0 Q ha-1, 29.4 Q ha-1 of the new rate, and blanket recommendation rate, respectively. In addition, the yields obtained from the farmers’ training center were 47.0 Q ha-1 and 33 Q ha-1 of the new recommendation rate and blanket recommendation rate, respectively. This might be due to the effective monitoring and follow-ups in the farmers’ training center than the farmers’ field. The result of the partial budget analysis revealed that adopting of newly recommended rate increases the overall profit, which is 8680 ETB per hectare. Therefore, it is better if increase the adoption rate of the newly recommended fertilizer rate on maize to improve the production and productivity of maize producers. Int. J. Agril. Res. Innov. Tech. 12(2): 96-100, December 2022